Acetalization of Enol Ethers with Alcohols under Visible Light Irradiation Using BINOLs as Photoacid Catalysts - Liu, Haonan; Chen, Yueyong; An, Deng; Zhang, Xun; Liao, Saihu (Synlett, 2022)
Appropriately substituted 1,1′-bi-2-naphthols (BINOLs) are demonstrated as effective photoacid catalysts for promoting the acetalization of enol ethers with alcohols under irradiation with visible light. The reactions proceed efficiently with a wide range of substrates under mild, near neutral conditions.
Keywords: BINOL; photoacids; acetals; visible light; acetalization